2020
DOI: 10.1187/cbe.20-03-0054
|View full text |Cite
|
Sign up to set email alerts
|

Student Behaviors and Interactions Influence Group Discussions in an Introductory Biology Lab Setting

Abstract: Students naturally take on different behaviors when engaged in group discussion of data, which sorts them into preferred roles. In discussions in which all students collaborate, groups generate more complete arguments to support conclusions. Without guidance, groups generally focus on analyzing data rather than building reasoned explanations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…, 2021 ) and how to reason ( Knight et al. , 2013 ; Paine and Knight, 2020 ). Our rich, qualitative work begins to provide the foundational knowledge needed to develop this guidance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2021 ) and how to reason ( Knight et al. , 2013 ; Paine and Knight, 2020 ). Our rich, qualitative work begins to provide the foundational knowledge needed to develop this guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Another way to possibly facilitate social metacognition during small-group problem solving is through the use and modification of group roles. Other researchers suggest that students’ natural role choices are not necessarily optimal and that consideration of group roles can improve group discussions ( Paine and Knight, 2020 ). In our study, students took on a defined group role as either recorder, presenter, or manager which are common group roles for a POGIL-style classroom ( Moog et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, although students may have been socially engaged, they may not have been behaviorally/cognitively engaged in the activity. Although students are thought to be more cognitively engaged when they are interacting with other students to create new material and build off each other’s ideas, one study found that student discussion more frequently centers around exchanging information instead of exchanging reasoning . Therefore, it would be informative for further research to explore how group dynamics and social interactions influence students’ overall, behavioral/cognitive, emotional, and social engagement.…”
Section: Implications For Researchmentioning
confidence: 99%
“…The detailed studies of these specific subcategories of reasoning have usually involved extensive interviews with students and/or very specific guidelines that prompt the use of a particular type of reasoning. Those who have explored students’ unprompted general use of reasoning have found that few students naturally use reasoning to support their ideas ( Zohar and Nemet, 2002 ; James and Willoughby, 2011 ; Schen, 2012 ; Knight et al , 2015 ; Paine and Knight, 2020 ). However, with explicit training to integrate their knowledge into mental models ( Kuhn and Udell, 2003 ; Osborne, 2010 ) or with repeated cueing from instructors ( Russ et al , 2008 ; Knight et al , 2015 ), students can learn to generate more frequent, specific, and robust reasoning.…”
Section: Introductionmentioning
confidence: 99%